Wormholes from beyond - Juliano C. S. Neves (European Physical Journal C: Particles and Fields)
Abstract In a brane-world context in which our universe would be a four-dimensional brane embedded into a five-dimensional spacetime or bulk, wormhole geometries are induced on branes. In this article, the Morris–Thorne wormhole and the Molina–Neves wormhole are obtained on the brane using the Nakas–Kanti approach, which starts from a regular five-dimensional spacetime to obtain known black hole and wormhole solutions on the four-dimensional brane. From the bulk perspective, these wormholes are five-dimensional solutions supported by an exotic fluid, but from the brane perspective, such objects are wormholes not supported by any fields or particles that live on the four-dimensional spacetime. Thus, the cause of these wormholes is the bulk influence on the brane.